A look into the word order of Malay and Mandarin compound words/phrases / Hoe Foo Terng … [et al.] - Terng, Hoe Foo; Heng, Lim Teck; Yih, Mah Boon; Marimuthu, Rasaya (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
There are many Malay students in Malaysia studying Chinese. In the process of learning, these Malay students are influenced by the negative transfer of their mother tongue when they write sentences, translate, and reorganize the words into Chinese sentences. As such, they will produce erroneous sentences. The authors opine that when Malay students learn the similarities and differences in the word order in Malay and Chinese phrases, the mistakes in making sentences, translating, and reorganizing words in Chinese sentences can be reduced. In this short article, firstly, an overview of the formation of compound words/phrases in the Malay and Chinese languages is presented. This is then followed by a brief description on the development in the teaching of translating Malay sentences into Chinese. The article ends with a summary on the comparison of the word order of nine categories of compound words/phrases in both languages. These nine categories of compound words/phrases are the common vocabulary found in the textbooks used in UiTM Mandarin courses. It is noted that when Malay compound words/phrases are translated into Chinese, compound words/phrases of these three combinations - noun-noun (of partial formal phrase structure), adjective-noun, and adverb-verb (“kata kerja - kata penerang” in Malay) - need to have their order of words changed. The compound words/phrases in six other groups, however, did not require any changes in the word order.